Synthesis of a novel bis-amino-modified thymidine monomer for use in DNA triplex stabilisation - Sollogoub, M; Dominguez, B; Fox, K; Brown, T (2000)
A novel thymidine analogue containing both 5-aminopropargyl and 2'-aminoethoxy modifications has been synthesised and incorporated into a triplex-forming oligonucleotide; the combination of the two amino groups on the same nucleoside greatly enhances triplex stability.